Comfort evaluation and position parameter optimization of the steering wheel in agricultural machinery based on a three-level evaluation index system - Wang, Qichao; Shang, Yujun; Qin, Zengzhi; Xu, Hongmei; Jiang, Wei; Li, Hang; Zhang, Guozhong (International Journal of Agricultural and Biological Engineering, 2022)
The aim of this study is to evaluate the comfort and optimize the position parameters of steering wheel. Taking the H point of driver as the reference point, three position parameters of steering wheel were determined, which were used as experimental factors. A comprehensive evaluation index system of the comfort was established. The comfort range and optimal levels of three parameters were determined by a single factor test, based on which a response surface optimization and validation test was carried out. The optimization and validation test results show that the expected comprehensive score of the comfort is 0.864, and the average relative error between the predicted and the measured value is 4.18%, indicating that the optimization results are reliable. The findings can provide reference for the comfort optimization design of steering wheel in agricultural devices.Keywords: agricultural equipment, steering wheel, comfort evaluation, position parameter optimizationDOI: 10.25165/j.ijabe.20221504.6318Citation: Wang Q C, Shang Y J, Qin Z Z, Xu H M, Jiang W, Li H, et al. Comfort evaluation and position parameter optimization of the steering wheel in agricultural machinery based on a three-level evaluation index system. Int J Agric & Biol Eng, 2022; 15(4): 214–222.